Popular Theatre - Highbrow or Lowbrow - Nygaard, Jon (Nordic Theatre Studies, 2018)
For 13 years, from 1851 to 1864, Ibsen worked full time at the Norwegian theatres in Bergen and Christiania (Oslo) as a stage director and theatre manager. Ibsen’s period in the theatre and the repertory he staged have seldom enjoyed much attention in scholarly research. The reason for this has been that the repertory Ibsen staged has been seen as vulgar and lowbrow, and Ibsen’s period in the theatre has almost unanimously been seen as a waste of time. The general understanding has been that Ibsen’s development as an artist had been much faster if he had been working with a highbrow repertory of serious drama. Contrary to this established opinion I will contribute to the discussion of popular theatre as highbrow or lowbrow by presenting the production A Caprice (En Kaprice) by Erik Bøgh, staged by Henrik Ibsen at the Norwegian Theatre in Christiania (Oslo). It premiered 7 September 1859 and then ran for another thirty-five performances during the 1859-60 season. The total number of attendances was more than 30.000. In relation to the population of the town of 42.000, it was about 2/3 or 67%. This is the by far largest box-office success in Norwegian theatre history. No wonder that Ibsen scholars generally have understood A Caprice as the ultimate example of the unholy trade Ibsen was forced into as a theatre manager. According to Michael Meyer Ibsen for the only time in his life “rebuked for truckling to the box-office” (Meyer 1971, 166). The contemporary criticism in Morgenbladet (Nr. 278, 9.10.1859) claimed that Ibsen was declining the Norwegian Theatre in Christiania into a kind of amusement ground for the lower classes. I will, however, present A Caprice as the summit of Ibsen’s theatrical career and underline that both this and other dance productions staged by Ibsen in this period, were not at all amusement for the lower classes but on the contrary important expressions of his artistic creativity and development – and actually a highbrow performance presented for an upper class audience.